Glycerol–Silicone Membranes for Sustained and Controlled Topical Delivery of Antimicrobial and Pain‐Relief Drugs. Issue 5 (18th January 2021) - Mazurek, Piotr; Frederiksen, Nikoline S.; Silau, Harald; Yuusuf, Nuura A.; Mordhorst, Hanne; Pamp, Sünje J.; Skov, Anne L.
Abstract: Controlling drug delivery from medical dressings to wounds remains a challenge despite the presence of multiple drug‐containing wound dressings on the market. The dressing should ideally be effective immediately after application and still show no burst effect, and must also be comfortable for an extended period of time. Here, a silicone‐based membrane is shown to offer an adjustable, constant release of various drugs even at a minimum moisture level resembling that of dry wounds. The drugs are dissolved in glycerol, which is speed‐mixed with silicone and subsequently cured to yield a solid membrane with evenly distributed glycerol microcontainers housing the drug. The drugs are released immediately upon contact with moisture, enabling efficient treatment with short response time and no burst. Drug delivery capability is evaluated using a classical drug release experiment, as well as by performing an antimicrobial susceptibility test on ten bacterial strains in agar diffusion assays. Results show that glycerol–silicone membranes are promising candidates for fighting bacterial infections. Moreover, the addition of glycerol domains to a silicone matrix is proven to have a positive impact on water vapor transmission rate and moisture handling capabilities, resulting in a more skin compliant dressing. Abstract : Glycerol–silicone membranes represent a platform technology for controlled delivery of actives substances to wounds. They enable release of virtually any drug such as antimicrobial, anti‐inflammatory or pain relief agents and thus enable treatment of various disorders. Here it is shown that the membranes are an efficient tool in fighting bacterial infections outperforming commercial state‐of‐the‐art wound dressings.